2023
DOI: 10.3390/cells12232737
|View full text |Cite
|
Sign up to set email alerts
|

Basosquamous Carcinoma: Comprehensive Clinical and Histopathological Aspects, Novel Imaging Tools, and Therapeutic Approaches

Giulia Murgia,
Nerina Denaro,
Francesca Boggio
et al.

Abstract: Basosquamous carcinoma (BSC), an uncommon and aggressive nonmelanoma skin cancer exhibiting characteristics ranging from basal cell carcinoma (BCC) to squamous cell carcinoma (SCC), is a subject of controversy in terms of its classification, pathogenesis, histologic morphology, biologic behavior, prognosis, and management. This narrative review is based on an electronic search of English-language articles in PubMed that included the terms “basosquamous carcinoma” and/or “metatypical carcinoma of the skin” in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
(230 reference statements)
1
2
0
Order By: Relevance
“…In this study, we observed an increased incidence of SCC and BSC in aged individuals with a history of sun exposure. Compared with the literature reporting that 82-97% of BSC cases occur in sun-exposed areas of the head and neck, with a prevalence in aged individuals [16], our study confirmed the prevalence for sun-exposed areas and older adults. Concerns about aging date back to 1939, when Walford introduced the theory of immunological aging.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we observed an increased incidence of SCC and BSC in aged individuals with a history of sun exposure. Compared with the literature reporting that 82-97% of BSC cases occur in sun-exposed areas of the head and neck, with a prevalence in aged individuals [16], our study confirmed the prevalence for sun-exposed areas and older adults. Concerns about aging date back to 1939, when Walford introduced the theory of immunological aging.…”
Section: Discussionsupporting
confidence: 85%
“…Although the available data classify SCC as the second most common skin cancer, with a constantly increasing worldwide prevalence [15], and BSC as a rare cancer which does not have a standardized approved therapeutic guidelines for the management [16], our experience has shown that BSC is not rare. Therefore, it requires a customized treatment protocol.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, LC-OCT has been gaining growing attention because it provides detailed microscopic insight into skin structures at a cellular level, thus playing a central role in the identification of BCC [ 22 ]. Recently, Gust et al [ 23 ] demonstrated that the accuracy of LC-OCT, especially in equivocal BCC, was higher compared to dermoscopy and that, surprisingly, the association between those techniques reached an accuracy similar to the gold-standard histology [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCC and BCC are non-melanoma skin cancer (NMSC) with similar pathogenesis: SCC develops through malignant proliferation of epidermal keratinocytes, while BCC arises from basal cells ( 19 22 ). Moreover, basosquamous carcinoma is described, which is characterized by a combination of clinical, dermoscopic, and histologic features from both BCC and SCC, as well as the presence of a transition zone ( 23 ). The malignization of keratinocytes may be associated with ultraviolet radiation, HPV infection, RAS/RAF/MEK/ERK and PI3K/AKT pathways ( 24 ).…”
Section: Discussionmentioning
confidence: 99%